Phosphinothiolates as Ligands for Polyhydrido Copper Nanoclusters. Issue 49 (5th October 2014) - Huertos, Miguel A.; Cano, Israel; Bandeira, Nuno A. G.; Benet‐Buchholz, Jordi; Bo, Carles; van Leeuwen, Piet W. N. M.
Abstract The reaction of [CuI(HSC6H4PPh2)]2 with NaBH4 in CH2Cl2/EtOH led to air‐ and moisture‐stable copper hydride nanoparticles (CuNPs) containing phosphinothiolates as new ligands, one of which was isolated by crystallization. The X‐ray crystal structure of [Cu18H7L10I] (L=−S(C6H4)PPh2) shows unprecedented features in its 28‐atom framework (18 Cu and 10 S atoms). Seven hydrogen atoms, in hydride form, are needed for charge balance and were located by density functional theory methods. H2 was released from the copper hydride nanoparticles by thermolysis and visible light irradiation.